Oppositions in Arabic proverbs : a lexicosyntactic perspective - Hassanein, Hamada (Penerbit Universiti Kebangsaan Malaysia, 2021)
Human beings are claimed to have a strong tendency for structuring their thoughts in terms of binary oppositions (Lyons, 1977). Binary oppositions, both canonical and non-canonical, have cross-linguistically been shown to perform textual functions in language and discourse (Jones, 2002; Davies, 2012; Hsu, 2015; Akşehirli, 2018, among many others). This study examines the discourse functions of oppositions in a dataset of oppositional pairs extracted from a collection of Arabic proverbs. Drawing on a synergy of Jones’s (2002), Davies’s (2012), and Hassanein’s (2018) syntagmatic typologies of antonymy and opposition, it tests the synergised typology on the dataset to quantify and exemplify the discourse functions of opposition therein and prove the interactivity of the syntactic environments. The study has shown ancillary opposition to be the preponderant function with far higher frequency distributions than the remaining ones. Two functions logged in Classical Arabic discourse (Hassanein, 2018) have also been logged in proverbial discourse. One function is subordination (one opposite is hypotactically appended to another) and the other is case-marking (both lexemes play oppositional case roles at syntactic and semantic levels). The analysis has also shown that the syntagmatic classification replicated in this study validates former classifications across languages, most notably English, Swedish, Japanese, Chinese, Serbian, Romanian, Turkish, and Persian. It has also been revealed that the syntactic frames of co-occurring oppositions play significant roles in proverbial categorisation and conceptualisation and support the argument that proverbs tend to pattern cultural units and schemas into parallel structural frames.